Celebrating the French Republic in the Courier de l'Egypte - Fezanur Karaagaclioglu (Journal of Festive Studies)
In this article, I examine how French revolutionary ideas and ideals were performed in occupied Egypt. At the level of display, the ancient sites were very visibly united under the French tricolor flag, which was a highly symbolic, essentially ritualistic act. They occupied a significant place during celebrations of the foundation of the republic. It was Napoléon's wish that the “époque mémorable” that established the republic would be celebrated in Egypt with great pomp. These celebrations each year occurred in a “time out of time” both for the French and the Egyptians: they had a claim to demonstrate how history was “correctly,” that is, rationally, to be perceived and understood, and how the future was to be progressively and politically imagined. The accounts of the festivals speak to an exceptional interaction and exchange that transformed time, space, and the historical narrative in Egypt and assigned roles to the French and the Egyptians, hence enhancing the performative aspect of the expedition. I draw on the terminology and theoretical frameworks offered by scholars of performance such as Alessandro Falassi, Richard Schechner, and Richard Bauman. I understand the French Revolution in the larger chronological and spatial context as a narrative event, and accounts of the celebrations as narrated events. The French ultimately aimed at influencing the way the Egyptians would give meaning to what was happening; at fixing the meaning of the French presence in Egypt; and at rearranging the structure of social, cultural, and political relations and perceptions.